Rationalities, Normative Production and Autonomic Challenges Post April 25th: the case of the Autonomous Region of Madeira (Revista Lusófona de Educação, 2024)
After the 25th of April 1974, the democratization of management was the reason to justify several of thereforms carried out at school without this having meant a slowdown in political and administrative centralization, visible in the excessive normative production that greatly contributes to limiting the true participation and autonomy of educational actors. In addition, there is the hegemonic presence of instrumental and mechanical rationalities in decisions shaped by neutrality, thereby impeding the critical, bold, and creative capacity that democracy includes. The democratization of the school, because understood as a project under construction, has to recognize as relevant a set of variables, whether they are those relating to the political agendas that guide the actions of leaders, the way of choosing their leaders, the distribution of power and the democratization of its organizational or management structures, as its development depends on them. The Autonomous Region of Madeira, as a privileged space for democratic management, as it reflects a reality that is influenced, but also influences, national educational policies,allows us to recognize the advantage that comes from acting within an autonomous context. In this way, the possibility of adaptation considering the needs and particularities of Madeira expresses the importance of political and administrative autonomy for the realization of democracy.Keywords: democratic management; rationalities; autonomy